2020
DOI: 10.1038/s41467-020-17856-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neuronal underpinnings of safety in numbers in fruit flies

Abstract: Living in a group allows individuals to decrease their defenses, enabling other beneficial behaviors such as foraging. The detection of a threat through social cues is widely reported, however, the safety cues that guide animals to break away from a defensive behavior and resume alternate activities remain elusive. Here we show that fruit flies display a graded decrease in freezing behavior, triggered by an inescapable threat, with increasing group sizes. Furthermore, flies use the cessation of movement of oth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 49 publications
(53 reference statements)
1
42
1
Order By: Relevance
“…Unlike the UAS and gal4 controls, females did not advance egg-laying in a group when T4 and T5 were blocked (Figure 4E), showing that T4 and T5 are necessary for group sensing. Lobula columnar (LC) neurons are an entry point for the circuit-level study of visual responses since it is the first layer where visual information about objects is decoded (Ferreira and Moita, 2020;Ribeiro et al, 2018;Wu et al, 2016). Having identified motion cues of group members as the leading source of the group effect on egg-laying, we investigated the role of visual projection neurons responsive to the movement of small objects like a flies: LC10 and LC11 (Ferreira and Moita, 2020;Keleş and Frye, 2017;Ribeiro et al, 2018;Wu et al, 2016).…”
Section: The Motion Detection Circuit Is Necessary For Egg-laying Advancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the UAS and gal4 controls, females did not advance egg-laying in a group when T4 and T5 were blocked (Figure 4E), showing that T4 and T5 are necessary for group sensing. Lobula columnar (LC) neurons are an entry point for the circuit-level study of visual responses since it is the first layer where visual information about objects is decoded (Ferreira and Moita, 2020;Ribeiro et al, 2018;Wu et al, 2016). Having identified motion cues of group members as the leading source of the group effect on egg-laying, we investigated the role of visual projection neurons responsive to the movement of small objects like a flies: LC10 and LC11 (Ferreira and Moita, 2020;Keleş and Frye, 2017;Ribeiro et al, 2018;Wu et al, 2016).…”
Section: The Motion Detection Circuit Is Necessary For Egg-laying Advancementmentioning
confidence: 99%
“…Lobula columnar (LC) neurons are an entry point for the circuit-level study of visual responses since it is the first layer where visual information about objects is decoded (Ferreira and Moita, 2020;Ribeiro et al, 2018;Wu et al, 2016). Having identified motion cues of group members as the leading source of the group effect on egg-laying, we investigated the role of visual projection neurons responsive to the movement of small objects like a flies: LC10 and LC11 (Ferreira and Moita, 2020;Keleş and Frye, 2017;Ribeiro et al, 2018;Wu et al, 2016). LC neurons were silenced in females by expressing Kir2.1 and by testing the focal female for egg-laying latency alone or in groups with wild-type males.…”
Section: The Motion Detection Circuit Is Necessary For Egg-laying Advancementmentioning
confidence: 99%
“…It is well known that the decision to freeze depends on several factors from the external and internal environment [23,24,[42][43][44][45]. In flies, we have shown that the animal's own behavioural state [11] and the social environment regulates threat-induced freezing [15]. Here, we show that two features of cardiac activity measured before threat, reversal rate and reversal variability, partially predict the amount of looming triggered freezing.…”
Section: Cardiac Activity As Modulator Of Freezingmentioning
confidence: 59%
“…Insects show a large repertoire of defensive behaviours, including freezing and fleeing responses, upon detection of a threat [11][12][13][14]. The fruit fly has become a very useful model to study the neuronal circuits of defensive behaviours, from the integration of cues of threat and surrounding context, to the selection and execution of the defensive responses [11,[14][15][16]. It has been previously postulated that threat induces a sustained change in the flies' internal state, akin to a primitive emotional state [17].…”
Section: Introductionmentioning
confidence: 99%
“…As protection from predators by diluting the risk of being targeted (Hamilton, 1971; Vine, 1971) is one of the key benefits of sociality it is a logical consequence of social isolation to increase vigilance and respond to potentially threatening stimuli at a lower threshold (Hawkley and Cacioppo, 2010). For example, fruit flies display a graded decrease in freezing in response to threatening stimuli that is proportional to group size (Ferreira and Moita, 2020). Our results suggest that Pth2 might contribute to the regulation of appropriate vigilance states in vertebrates.…”
Section: Discussionmentioning
confidence: 99%